BIOAKTIVITAS ASAM JAWA (Tamarindus indica) DAN PEMANFAATANNYA - Silalahi, Marina (UNIVERSITAS PGRI MADIUN, 2020)
Tamarindus indica is one of the species in the Fabaceae which is widely used as food and traditional medicine. T. indica has naturalized in Indonesia, especially in Java Island and mostly only used as food, while its use as medicine is still limited. This study aims to explain the relationship between the use of T. indica as a traditional medicine and its bioactivity. The method used in this study is based on literature studies obtained online using the key word Tamarindus indica, uses of T. indica and bioactivities of T. indica. The use of T. indica as a traditional medicine is related to its bioactivity. Bioactivity of T. indica as antimicrobial, antidiabetic mellitus, anti-cholesterol, analgesic, antiobesity and antioxidant. Bioactivity of T. indica as anti-microbial and anti-cancer has the potential to be developed as a food preservative as well as providing healthy effects